Hemobilia due to angiocolytic abscess of liver - Balboa, Oscar; Trostchansky, José; Valls, Alberto (Cirugía del Uruguay, 1973)
A patient had repeated biliary-tract operations and during the cours e of supurated choliangitis due to riOsidual lithiasis of choledocus, was found to have frorn hemobile. This is a rare consequence of a· hepatic abscesses, pathogeny resulted in septic necrosis of hepatic walL Its origin may lie not only in erosion of a large vessel but also in bleeding of granulation tissue. Adequate treatment of inicial disease is deemed important. However, exact topographic diagnosis is difficult.